Perceived Utility of the RE-AIM Framework for Health Promotion/Disease Prevention Initiatives for Older Adults: A Case Study from the U.S. Evidence-Based Disease Prevention Initiative - Ory, Marcia G.; Altpeter, Mary; Belza, Basia; Helduser, Janet; Zhang, Chen; Smith, Matthew Lee (Frontiers in Public Health, 2015)
*